PERAMALAN PERTUMBUHAN PENDUDUK KABUPATEN SITUBONDO DENGAN MODEL ARIMA, DERET ARITMATIK, DERET GEOMETRI DAN DERET EKSPONENSIAL “THE FORECASTING GROWTH OF THE POPULATION IN SITUBONDO BY USING ARIMA, ARITMATICS, GEOMETRICS AND EXPONENTIAL” - As’ad, A; Tirta, I Made; Dewi, Yuliani Setia (Department of Mathematics Education , University of Jember, 2013)
Abstract. ARIMA models as the population forecasting in Situbondo is a model of ARIMA(3, 3, 3) and mathematically, it is stated as; =2,445–1,6632–0,148+0,9732–1,0746+ 0,4676+– 1,0635. Forecasting the population in Situbondo is 667646 people in 2012 and in 2013 is 677852 people. Some other approaches in determining the population is the Arithmetic growth formula, the result of forecasting in 2012 is 657540 people and in 2013 is 661626 people, Based on Geometric growth formula, the result of forecasting in 2012 is 19696459 people and in 2013 is 35211214 people and Based on Exponential growth formula the result of forecasting in 2012 is 657611 people and in 2013 is 661799 people. If we compare the data of the forecasted result of ARIMA model with the Aritmatics growth formula and Exponential growth formula, show that the data of the population with the last ten actual data is relatively similiar.The closed last ten actual data forecasting of population is the aritmatics growth formula, whereas the data of the population result for next two year based on the Geometric growth formula got the forecasted result which is different from the forecasted result of ARIMA model, Aritmatics growth formula and Exponential growth formula. Key Words:forecasting, arima models, arithmetic, geometric, exponential